Conversion and Reversion Rates of Tuberculosis Screening Assays in Patients With Rheumatic Diseases and Negative Baseline Screening Under Long-Term Biologic Treatment - Konstantinos Thomas; Emilia Hadziyannis; Chrisoula Hatzara; Anastasia Makris; Christina Tsalapaki; Argyro Lazarini; Kalliopi Klavdianou; Katerina Antonatou; Christos Koutsianas; Dimitrios Vassilopoulos (Case Western Reserve University, 2020)
Background: To determine the conversion and reversion rates of tuberculosis (TB) screening tests (Tuberculin Skin Test-TST, Interferon Gamma Release Assay-IGRA: T-SPOT.TB) during biologic treatment in patients with rheumatic diseases and negative baseline screening. Methods: This was a long-term, longitudinal cohort study of 50 patients with rheumatic diseases and negative baseline TB screening (TST: < 5 mm, negative T-SPOT.TB) treated with tumor necrosis factor inhibitors (TNFi) or other non-TNFi biologics. Patients were rescreened at a mean time of 1.4 (first rescreening) and 6.9 (second rescreening) years from baseline, with both assays. The conversion (negative to positive) and reversion (positive to negative) rate was calculated for each TB screening test. Results: Fifty patients (mean age = 60 years) with various rheumatic diseases (rheumatoid arthritis: n = 24, spondyloarthropathies: n = 23, other: n = 3) were enrolled. During the first phase (baseline to first rescreening), all patients were treated with TNFi while during the second phase (first to second rescreening), TNFi (54%) and non-TNFi (46%) were used. Fifteen patients (30%) displayed conversion of at least 1 screening assay during follow-up (10 at the first and 5 at the second rescreening). This conversion rate was higher with TST (n = 11, 22% or 3.47/100 patient-years) compared to T-SPOT.TB (n = 4, 8% or 1.74/100 patient-years). Among the 10 converters at the first rescreening, 5 received isoniazid (INH) preventive therapy and 5 did not; an equal number of patients (3/5, 60%) reverted to negative with or without INH therapy. None of the patients developed active TB during follow-up (6.9 ± 1.0 years). Conclusions: Approximately one-third of patients with rheumatic diseases and negative baseline TB screening developed conversion of at least 1 screening test during long-term biologic treatment. This occurred most often with TST and was usually a transient event. These findings do not support routine serial TB retesting in biologic-treated patients with rheumatic diseases in the absence of TB risk factors.